IMPLEMENTASI METODE AT-TARTIL DALAM PEMBELAJARAN QIRO’ATUL QUR’AN KELAS 3 DI MI MUJAHIDIN PARIMONO JOMBANG - Vivi Afbrifani; Izzah Is'adah (Abnauna: Jurnal Ilmu Pendidikan Anak, 2022)
The Qur'an is the holy book of Muslims which was revealed to the Prophet Muhammad SAW. through the angel Gabriel. Seeing the low interest in learning to read the Qur'an in this modern era, KH. Imam Shafi'I, KH. Fahruddin Sholih, and KH. Masykur Idris tries to make practical learning, CBSA (an active way of learning for students), and uses drills. With a relaxed but organized learning system, it is hoped that it can encourage the spirit of learning to read the Qur'an in this modern era. Based on the statement above, the authors are encouraged to conduct research on "Implementation of the At-Tartil Method in Learning Qiroatul Qur'an at MI Mujahidin Parimono Jombang". The results of the discussion of this thesis are aimed at: 1) Describe the application of the At-Tartil method in learning Qiroatul Qur'an at MI Mujahidin Parimono Jombang. 2) Describe the effect of the At-Tartil method in learning Qiro'atul Qur'an on the learning achievement of MI Mujahidin Parimono Jombang students. 3) Explain what factors support and hinder the implementation of the At-Tartil method in learning Qiro'atul Qur'an. For this reason, the author uses a qualitative descriptive approach and data collection techniques using interviews, observation, and documentation. The efforts of educators in applying the At-Tartil method. The results of this study can be concluded that: Implementation of the At-Tartil Method in Learning Qiroatul Qur'an at MI Mujahidin Parimono Jombang. Achievement in reading the Qur'an. As well as the factors supporting and inhibiting the implementation of the At-Tartil method in learning Qiro'atul Qur'an at MI Mujahidin Parimono Jombang.